If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 + 6x = 82 Reorder the terms: 2 + 4x + 6x = 82 Combine like terms: 4x + 6x = 10x 2 + 10x = 82 Solving 2 + 10x = 82 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 10x = 82 + -2 Combine like terms: 2 + -2 = 0 0 + 10x = 82 + -2 10x = 82 + -2 Combine like terms: 82 + -2 = 80 10x = 80 Divide each side by '10'. x = 8 Simplifying x = 8
| -5d+120=-6d-9 | | 8(3G+5R)= | | 14+29m=28+22m | | -8x-22=-3(x-1) | | 4x+17=90 | | 2f+20=101-f | | 2w-18w=-32 | | 32+12y=420 | | 78=3c+12+-1c+4 | | -139=5x+7+5 | | x-38=84 | | 3m+167=55+4m | | 12y+22=9y | | 3x(x+20)=44 | | -11+8x=-67 | | -2p+28=6p-44 | | -6(x+2)-13=10+1 | | (-10x+35)*(5)=x | | 9t=42 | | 9(-8)-4((-8)-7)= | | -2x+7+7x=-3 | | -65+2x=33-5x | | 7c-4c=78+12 | | 34-5x=-21 | | 6y-90=5y-75 | | 5(t-6)+5t=5(2t+2)-9 | | (-10x+35)*(5)= | | (6-2c)+(3c-4)= | | 0.5+0.7=-0.75 | | 4h=5h-60 | | 3x+18=4x+13 | | y=(2t(5-t)) |